The pH of the vaginal environment and phase-contrast microscopy of cytological smears in women after menopause - Malarewicz, Andrzej; Szymkiewicz, Jadwiga; Sola, Michał; Błaszczak, Marta (Menopause Review/Przegląd Menopauzalny, 2011)
Taking into account the fact that so far the boundary value of the maturation index (MI), above which hypoestrogenism in the organism can be found with absolute certainty, has not been unambiguously determined and that such a boundary has also not been determined for the pH of the vaginal environment, it was decided to find out how the values of the mentioned indices behave in women at different periods after the menopause. We also decided to determine how the Lactobacillus vaginalis bacteria behave at different periods after the menopause. The investigation was conducted in 114 women in total. The vaginal pH was assessed using colorimetric indicator strips (Merck, Germany). After collecting the vaginal smears both the maturation indices of the epithelial cells and the behaviour of Lactobacillus bacteria were appraised under the phase-contrast microscope, and the number of bacteria was determined using a Nugent scale. The analyses of the results of our research permit the following conclusions: 1. The inspection of vaginal smears using phase-contrast microscopy is a fast and precise way of quantitative assessment of the behaviour of different kinds of stratified squamous epithelium of the vagina and the degree of colonization of the vagina with the acid-forming bacteria Lactobacillus vaginalis. 2. The finding that more than 15% of cells originated from the basal layer and no more than 7% from the surface of the stratified epithelium in the vaginal smears and that the values of acidity of the vaginal environment are above pH 5 is characteristic for women more than five years after the onset of the menopause. 3. In the course of aging of the women as the years go by, starting from 5 years after menopause, the normal forms of Lactobacillus vaginalis tended to disappear and only the polymorphic and involution forms lived in the vagina, and a complete lack of them was revealed in the senior women (more than 25 years after the menopause).